Hubungan antara Pengetahuan Dasar Pendidikan Agama Islam Dasar dan Matematika Dasar Mahasiswa - Eliyah - Arhadi (Arfannur, 2021)
RELATIONSHIPS BETWEEN KNOWLEDGE EDUCATION OF BASIC ISLAMIC RELIGION AND BASIC MATHEMATICS OF STUDENTS. This study aims to prove that there is a significant relationship between basic Islamic religious education knowledge and basic mathematics knowledge of students. The method used is a quantitative method of correlation type with the survey method as a field data collection method. From the data analysis conducted, several research findings were obtained that; 1. Basic Islamic Religious Education knowledge (X) has a significant relationship with the basic Mathematics knowledge (Y) of students at the Tarbiyah Faculty of Education and Teacher Training. The amount of correlation obtained by Product Moment analysis from Pearson or test r = 0.549. When compared with the correlation coefficient interpretation table, the value of 0.549 or 54.9% is in the "low" category. 2. The determinant coefficient (KD) or R2 is 0.301 or 30.1%. This means that the basic Islamic Education Knowledge variable explains the variable basic Mathematics knowledge of students by 30.1%, while 69.9% is influenced by other variables. 3. The form of the relationship that occurs is a positive relationship, symbolized by the symbol "positive" in the correlation coefficient between variable (X) and variable (Y). A positive relationship can also be interpreted as a one-way relationship. That is, if students 'basic Islamic education knowledge increases, the students' basic Mathematics knowledge will also increase.